Nano and micro porous GaN characterization using image processing method - Ahmed, Naser Mahmoud; Ramizy, Asmiet; Hassan, Z.; Ali, Amer; Khalib, Omar; Yarub, Al-Douri, Prof. Madya Dr. (Elsevier GmbH, 2012)
Link to publisher's homepage at http://www.elsevier.com/